Analysis of Venture Capital Funding in India - Khosla, Dimple (Gyan Management Journal, 2015)
One of the most important developments in entrepreneurship has been growth of Venture Capital over  the past decade. It has had a profound impact on the world economy in terms ofjob creation, innovative  products and services, competitive vibrancy and enhancement of entrepreneurial spirit. It has played a  catalytic role in entrepreneurship by disseminating and creating fundamental values that trigger and  sustain economic growth and renewal. Specifically, venture capitalists help their investee companies in  providing a network, recruiting key management and building a team, developing financial systems,  advising on company law and other legal matters, helping co-investment and arranging working  capital facilities from bankers, providing marketing links and contacts, sharing the business  perspective, providing support and confidence during bad times, helping in long term strategic  thinking and planning, helping to create an entrepreneurial climate and devising incentive systems to  promote long-term team work. In India, the level of growth has not been found so promising and  consistent due to lack of financing the innovative ideas. To get the full advantage of economic reforms  and to make the Indian economy more competitive, it is high time that the catalytic role of Venture  Capital must be clearly understood. Present study has been undertaken to see in which industry, region,  area or stage venture capitalist provide their finance.
Keywords: Venture Capital; private equity; innovative; risk finance; entrepreneurship; investment